L'intervento Italiano in Carinzia dopo la Prima guerra mondiale e i britannici - Bajc, Gorazd (Acta Histriae, 2020)
Based on the analysis of selected preserved materials housed in the Archive of the Republic of Slovenia the present contribution discusses "self-evaluations" of the Slovenian State Security Service with respect to monitoring the activities of the British Intelligence Agency on the territory of the Socialist Republic of Slovenia in the period between the 1960s and the late 1980s. The authors analyse those intelligence reports which pertained to reporting on the agency's own activities and could thus be described as assessments of the (un)successfulness in its surveillance of British diplomats, media, and citizens visiting Slovenia at the time, and the Slovenian/Yugoslav emigrants in Great Britain.
Keywords: Carinthia; Carinthian plebiscite; Carinzia; Croats and Slovenes; ferrovie; Gran Bretagna; Great Britain; Italia; Italija; Italy; Kanalska dolina; Kingdom of Serbs; Koroška; koroški plebiscit; Kraljevina Srbov, Hrvatov in Slovencev; plebiscito carinziano; railways; Regno dei serbi, croati e sloveni; Val Canale; Velika Britanija; železnice